Species composition and stand structure of Dipterocarpaceae in Chini watershed forest, Pekan, Pahang, Malaysia - Zohari, Ahmad Fitri; Kamin, Kamilah Hanani; Nik Hashim, Nik Hazlan; Nik Ali, Nik Norafida; Kholid, Mohd Azman; Mohd Nor, Ahmad Muttaqin; Engku Ariff, Engku Azlin Rahayu; Mohamad, Abdul Latiff (Universiti Teknologi MARA (UiTM), 2023)
A study was conducted in the Chini Watershed Forest, Pekan, Pahang, to assess the species composition, stand structure, distribution, and total biomass of Dipterocarpaceae. The primary objective was to understand the ecological characteristics of this important forest ecosystem. Five plots, each measuring 25 x 20 m, were randomly selected, covering a total area of 0.25 ha. Within each plot, all trees with a diameter at breast height (DBH) of ≥ 5.0 cm were tagged and measured. A total of 27 individual trees belonging to Dipterocarpaceae were recorded, representing three genera and ten species. Shorea emerged as the dominant genus with six species, alongside Hopea and Vatica. The stand structure analysis revealed that 55% of all individuals fell within the lowest DBH class (5.0 - 14.9 cm), indicating a relatively young population. In terms of density, Shorea maxwelliana exhibited the highest density at 24 individuals per hectare. Among the species, Hopea griffithii had the highest frequency, present in four out of the five plots, with a frequency of 80%. The basal area (BA) was determined to be 10.08 m2/ha, with Shorea leprosula having the highest basal area at 4.17 m2/ha at the species level. These findings contribute to our understanding of the Dipterocarpaceae community in the Chini Watershed Forest and may have implications for its ecological management and conservation.